Meningkatkan Keterampilan Bernalar Kritis Siswa SMP Pangudi Luhur Wedi Kelas 8B Menggunakan Model Discovery Learning Berbantuan Multimedia - Teresia Sandra Maria; Yohanes Umbu Lede (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education is the most important factor in determining the quality of human resources and the progress of a nation. The educational process is able to give birth to creative, innovative ideas in the dynamics of current developments. In the education process, curriculum development becomes one of the instruments to improve the quality of education. With this research, it is hoped that students will be able to improve their critical reasoning skills using the Multimedia-Assisted Discovery Learning Model. Apart from that, it is hoped that students can combine daily life in dealing with suffering with the tribulations experienced by Jesus so that they can apply Jesus' example in their daily life. The method used in this research is Classroom Action Research which includes planning, implementation, observation and reflection. In this research, it was found that students' critical reasoning skills can be improved through multimedia prepared by teachers, making the learning process and understanding of the material easier. Multimedia assistance can also increase concentration during learning because it is more interesting